2020
DOI: 10.35836/jakis.v8i2.119
|View full text |Cite
|
Sign up to set email alerts
|

Efisiensi Bank Umum Syariah Di Indonesia Dengan Pendekatan Three Stages Frontier Analysis

Abstract: Efficiency is one of the parameters to measure the performance of the banking industry. This paper is using three stages to find out how the conditions of efficiency level of Islamic banking. Frontier and Stochastic Frontier Approaches are used to calculate the efficiency level and then averaged. Last, the determinants of efficiency were conducted by the Tobit Model. The data are 7 Sharia Commercial Banks during the period 2010 to 2017 which are chosen by purposive sampling. The study found the average efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
1
1
0
1
Order By: Relevance
“…Therefore, those variables have no significant effect on efficiency. The study results align with research conducted by Muttaqin et al (2020), which revealed that CAR and NPF had no significant effect on efficiency. Similarly, the research by Octrina and Mariam (2021) found that ROA and NOM had no significant effect on efficiency.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, those variables have no significant effect on efficiency. The study results align with research conducted by Muttaqin et al (2020), which revealed that CAR and NPF had no significant effect on efficiency. Similarly, the research by Octrina and Mariam (2021) found that ROA and NOM had no significant effect on efficiency.…”
Section: Discussionsupporting
confidence: 87%
“…Islamic banks are a rapidly growing industry (Bitar, Hassan, and Walker 2017). The banking industry plays a crucial role in efficiency in Islamic banking, one of the parameters used to measure performance (Muttaqin, Rini, and Fatriansyah 2020). The Islamic financial industry worldwide has experienced significant growth since 25 years ago compared to conventional banks.…”
Section: Literature Review Islamic Banking Efficiencymentioning
confidence: 99%
“…Estimasi nilai efisiensi perbankan syariah dilakukan dengan metode SFA, kemudian dilanjutkan dengan regresi linier dengan variabel independennya adalah size, ROA, NOM, NPF, FDR, CAR, Inflasi, GDP, dan BI Rate. Muttaqin, Rini, & Fatriansyah (2020) menggunakan rerata estimasi nilai efisiensi dari dua metode (SFA dan DEA) dan menggunakan determinant factor seperti sebelumnya, dengan tambahan satu variabel tambahan yaitu jumlah cabang (branch). Sementara itu beberapa penelitian menggunakan two stage model dengan metode DEA yaitu Firdaus & Hosen (2013), Puspita & Shofawati (2018), Fiafifah & Darwanto (2019), dan Kurnianti & Musdholifah (2019) dengan Tobit regression, Havidz & Setiawan (2015) dengan PLS, Bisri (2016) dengan fixed effect regression, Reza, (2016) dan Ramly & Hakim (2017) dengan panel regression.…”
Section: Gambar 2 Proporsi Pemilihan Objek Penelitianunclassified